Low-Power Laser Therapy in the Prevention of Induced Oral Mucositis: Literature Review - Rampini , Mariana Pereira (2009)
The usage of chemotherapy and radiotherapy isolated or together as protocol for oncology treatment may induce oral mucositis, which is one of the main acute side effects observed in patients who presented cancer. Such toxicity appears, in average, from seven to ten days after chemotherapy and from the second week of radiotherapy. Although it has been a highly studied toxicity, only recently have the molecular mechanisms started to be discovered, which has assisted the appearance of new protocols to prevent it. Among the therapeutic methods studied to prevent oral mucositis and several unsuccessful cases, the low power laser therapy has received good reviews as an efficient alternative in the prevention and treatment of oral mucositis presented as a low cost non-traumatic treatment, with good results. Various randomized studies with patients who underwent bone marrow transplants and radiotherapy in the region of the head and neck have proved the decrease of oral mucositis incidence as well as a decrease of pain during treatment. The objective of this paper is to revisit some concepts on mucositis and to review the literature concerning the clinical studies that have used low power laser in order to prevent oral mucositis.